Sinonasal Issues After Maxillectomy With Free Flap Reconstruction: Incidence and Clinical Approach. (30th June 2021) - Lerner, David K.; Filimonov, Andrey; Filip, Peter; Liu, Katherine; Russell, Stephen; Shah, Janki; Spock, Todd; Schaberg, Madeleine; Del Signore, Anthony; Colley, Patrick; Govindaraj, Satish; Khan, Mohemmed Nazir; et al.
Abstract : Objective: To characterize the clinical features associated with sinonasal complaints after maxillectomy with free flap reconstruction as well as propose a screening and treatment algorithm. Methods: Retrospective review of patients who underwent maxillectomy and free flap reconstruction at a tertiary care center. Results: Fifty‐eight patients were included, 25 (43.1%) of them had documented sinonasal complaints postoperatively. Eleven patients subsequently underwent revision surgery for sinonasal complaints. Among the 25 patients with sinonasal complaints, 22 patients (88.0%) had nasal crusting, 17 (68.0%) had nasal obstruction, 12 (48.0%) had rhinorrhea, 9 (36.0%) had facial pain or pressure, and 7 (28.0%) had foul odor. Twenty‐two patients (88.0%) had multiple sinonasal complaints. There was a higher incidence of both sinonasal complaints and surgical intervention in patients who underwent adjuvant radiation, but this was not statistically significant (47.7% vs 28.6%, P  = .235; 29.4% vs 7.1%, P  = .265). Conclusions: Sinonasal complaints are common following free flap reconstruction for a maxillectomy defect and should be screened for at postoperative visits, with early referral to a rhinologist for consideration of endoscopic sinus surgery. Nonsurgical treatment strategies include large‐volume nasal saline irrigations, xylitol irrigations for persistent inflammatory symptoms, and culture‐directed antibiotic irrigations for persistent infectious symptoms. Level of Evidence: 4 Laryngoscope, 132:67–72, 2022